Preface to the Special Issue on Sequential Code Parallelization - Wang, Chao; Nedjah, Nadia; Mourelle, Luiza M.; Wang, Aili (International journal of parallel programming, 2016)
Issue Title: Special Issue on Sequential Code Parallelization